Ethical Values in the Nursing Profession as Perceived by Head Nurses and Staff Nurses in Public Hospitals, Banda Aceh, Indonesia: A comparison Study - Yullyzar, Yullyzar; Nasae, Tasanee; Chaowalit, Aranya (Department of Nursing, Faculty of Medicine, Diponegoro University, 2014)
Purpose: Identify the levels of importance of ethical values in the nursing profession as perceived by the head nurses and the staff nurses, and compare the levels of importance of ethical values in the nursing profession as perceived by head nurses and those as perceived by staff nurses in public hospitals, Banda Aceh, Indonesia.Methods: Data collected from79 head nurses and 280 staff nurses were analyzed by using descriptive statistics and Mann-Whitney U test.Results: The total mean score of the importance of ethical values in the nursing profession perceived by head nurses and staff nurses are at a high level. The top 3 mean scores of the importance of ethical values in the nursing profession perceived by head nurses included caring, autonomy, and confidentiality. Meanwhile, the top 3 mean scores of the importance of ethical values in the nursing profession perceived by staff nurses included caring, confidentiality, and non maleficence. The Mann-Whitney U test showed that head nurses perceived accountability as significantly statistically different from staff nurses. Conclusion: Although head nurses and staff nurses mostly perceived the importance of ethical values in the nursing profession at high levels, it is still need to promote some ethical values of head nurses and staff nurses.